Can algae contribute to the war with Covid-19?. Issue 1 (1st January 2021) - Chia, Wen Yi; Kok, Hanz; Chew, Kit Wayne; Low, Sze Shin; Show, Pau Loke
ABSTRACT: The world at large is facing a new threat with the emergence of the Coronavirus Disease 2019 (COVID-19) pandemic. Though imperceptible by the naked eye, the medical, sociological and economical implications caused by this newly discovered virus have been and will continue to be a great impediment to our lives. This health threat has already caused over two million deaths worldwide in the span of a year and its mortality rate is projected to continue rising. In this review, the potential of algae in combating the spread of COVID-19 is investigated since algal compounds have been tested against viruses and algal anti-inflammatory compounds have the potential to treat the severe symptoms of COVID-19. The possible utilization of algae in producing value-added products such as serological test kits, vaccines, and supplements that would either mitigate or hinder the continued health risks caused by the virus is prominent. Many of the characteristics in algae can provide insights on the development of microalgae to fight against SARS-CoV-2 or other viruses and contribute in manufacturing various green and high-value products. Graphical Abstract: uf0001